Short hydrocarbon stapled ApoC2-mimetic peptides activate lipoprotein lipase and lower plasma triglycerides in mice - Sviridov, Denis; Dasseux, Amaury; Reimund, Mart; Pryor, Milton; Drake, Steven K.; Jarin, Zack; Wolska, Anna; Pastor, Richard W.; Remaley, Alan T. (Frontiers in Cardiovascular Medicine, 2023)
Introduction Defects in lipolysis can lead to hypertriglyceridemia, which can trigger acute pancreatitis and is also associated with cardiovascular disease. Decreasing plasma triglycerides (TGs) by activating lipoprotein lipase (LPL) with ApoC2 mimetic peptides is a new treatment strategy for hypertriglyceridemia. We recently described a dual ApoC2 mimetic/ApoC3 antagonist peptide called D6PV that effectively lowered TG in several mouse models but has limitations in terms of drug development. The aim of this study was to create the next generation of ApoC2 mimetic peptides. Methods We employed hydrocarbon staples, as well as select amino acid substitutions, to make short single helical mimetic peptides based on the last helix of ApoC2. Peptides were first tested for their ability to activate LPL and then in hypertriglyceridemia mouse models. All-atom simulations of peptides were performed in a lipid-trilayer model of TG-rich lipoproteins to discern their possible mechanism of action. Results We designed a single stapled peptide called SP1 (21 residues), and a double stapled (stitched) peptide called SP2 (21 residues) and its N-terminal acylated analogue, SP2a. The hydrocarbon staples increased the amphipathicity of the peptides and their ability to bind lipids without interfering with LPL activation. Indeed, from all-atom simulations, the conformations of SP1 and SP2a are restrained by the staples and maintains the proper orientation of the LPL activation motif, while still allowing their deeper insertion into the lipid-trilayer model. Intraperitoneal injection of stapled peptides (1–5 umoles/kg) into ApoC2–hypomorphic mice or human ApoC3-transgenic resulted in an 80%–90% reduction in plasma TG within 3 h, similar to the much longer D6PV peptide (41 residues). Other modifications (replacement L-Glu20, L-Glu21 with their D-isomers, N-methylation of Gly19, Met2NorLeu and Ala1alpha-methylAla substitutions, N-terminal octanoylation) were introduced into the SP2a peptide. These changes made SP2a highly resistant to proteolysis against trypsin, pepsin, and Proteinase K, while maintaining similar efficacy in lowering plasma TG in mice. Conclusion We describe a new generation of ApoC2 mimetic peptides based on hydron carbon stapling that are at least equally potent to earlier peptides but are much shorter and resistant to proteolysis and could be further developed into a new therapy for hypertriglyceridemia.